"Brain gain" on Wikipedia: Immigrants return knowledge home - Olga Slivko (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
Economic literature acknowledges the impact of immigration on cross-border patenting and scientific publications. However, the role of immigration ows in the dissemination of knowledge in a broader sense is yet to be assessed. In this paper, I estimate the effect of immigration on the facilitation of online knowledge reagrding destination countries in the native languages of immigrants. To quantify online knowledge, I focus on one of the world's most viewed online knowledge platforms, Wikipedia. I combine data on immigration ows between the pairs of immigrants' origin and destination countries with contributions to Wikipedia describing the countries of immigrants' destinations in the languages spoken in immigrants' origin countries. I specifically focus on knowledge domains describing science and culture. In order to draw a causal inference, I use shocks to immigration due to economic and political crises as exogenous shocks to Wikipedia content and analyze subsequent changes in the contributions to Wikipedia. An increase in immigration yields more knowledge contributed to Wikipedia about science and culture in destination countries in the native languages of the origin countries. Interestingly, the increase in contributions is driven by anonymous contributors. In the Wikipedia community, these are considered occasional contributors who care personally about the topics they contribute to. The increase in content generated anonymously is driven by longer contributions.
urn:nbn:de:bsz:180-madoc-456631
Keywords: L17; O15; O33; O35; H41; L86; 330; Immigration; Knowledge dissemination; Online knowledge; Wikipedia